High glycosylated hemoglobin level as a risk factor of latent tuberculosis infection in patients with uncomplicated type 2 diabetes mellitus - Arliny, Yunita; Yanifitri, Dewi Behtri; Mursalin, Diennisa (Universa Medicina, 2022)
Background Diabetes mellitus (DM) is known to increase the risk of infection including tuberculosis (TB). Some studies also showed that 2-15% of latent TB infection (LTBI) will progress to active TB. This study aimed to obtain the prevalence of LTBI and to determine the risk factors of LTBI in patients with type 2 diabetes mellitus (T2DM). Methods This was a cross-sectional study on 242 adult T2DM patients. For LTBI screening we performed the interferon gamma release assay (IGRA) (Quantiferon TB Gold Plus test) and for confirmation of active TB (pulmonary TB) we performed GeneXpert MTB/Rif sputum examination and chest X-ray. Glycosylated hemoglobin (HbA1c) levels, smoking history and BCG scar were collected. Multivariate logistic regression was used to analyze the data. Results Positive IGRA results were found in 99 of 242 uncomplicated T2DM patients while LTBI was found in 82 patients (33.8%). There were significant differences between T2DM patients with latent TB and T2DM patients without infection in HbA1c and specific IFN-Ã£ levels (TB1 minus nil and TB2 minus nil), i.e. 8.5% and 7.6%, 2.5 IU/mL and 0.06 IU/mL, and 2.6 IU/mL and 0.08 IU/mL, respectively. Multivariate analysis showed that the risk factors for LTBI in T2DM patients were smoking history, HbA1c >7%, and no BCG scar. Conclusions Because LTBI is prevalent in T2DM, it is important to screen for it in T2DM patients due to the risk of developing severe active TB. Absence of a BCG scar and high HbA1c levels are strong predictors of LTBI in T2DM patients.